The Steps Of Forming Of Solid Solution Noted (PZT-PSN-YMN) And Structural Characterization Of These Ceramic Materials - Oum keltoum, KRIBAA; Ahmed, BOUTARFAIA (Science des matériaux (Laboratoire LARHYSS); Vol. 9 No 01 (2017): Science des matériaux (Laboratoire LARHYSS) Moi de Mai, 2017)
This work is aimed to synthesize nano ceramic material of general formula short PZT-PSN-YMN of structure perovskite near the morphotropic phase boundary. These ceramics worked out by solid way, we present the preparation and the different stages of reaction mechanism of formation. Then we will detail the different techniques of analysis applied to this compound; we begin by the X-ray diffraction in the following by analysis spectroscopic (FTIR), laser particle size distribution and analysis by scanning electron microscopy (SEM).. These studies help us to accumulate as much information on the microstructure, the average particle size for all materials studied ceramic is less than 0.1μm. this value decreases after the heat treatment , beginning of forming the phase : PbTiO 3 from the calcination temperature 450 ° C ,PbZrO 3   from the calcination temperature 550 ° C and the formation and stabilization of the solid solution Pb(Ti,Zr)O 3 noted PZT at the temperature 900 °C. .